Managing NAFLD in Type 2 Diabetes: the effect of lifestyle interventions - Parry, S; Hodson, L (Springer Nature, 2020)
The prevalence of non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes (T2D) is increasing. As a strong association between these two diseases exist, it is unsurprising that the number of patients with coexisting NAFLD and T2D is also increasing. These patients display a deleterious metabolic profile (e.g. hypertriglyceridemia), and increased mortality rates relative to those with only NAFLD or T2D in isolation, therefore effective treatment strategies are required. Here we review the available intervention studies that have investigated changes in lifestyle (diet and exercise/physical activity) on metabolic parameters in patients with both NAFLD and T2D. Based on the available evidence, it appears that the addition of any kind of exercise (i.e. resistance, aerobic, or high-intensity intermittent exercise) is beneficial for patients with both NAFLD and T2D. These effects appear to occur independently of changes in bodyweight. Hypocaloric diets leading to weight loss are also effective in improving metabolic parameters in patients with both NAFLD and T2D, with data indicating that ~7-10% weight loss is required in order to observe beneficial effects. It is unclear if multidisciplinary interventions incorporating changes in both diet and physical activity levels are a more effective treatment strategy in this population than diet or exercise interventions in isolation. In conclusion, it is clear that lifestyle interventions are an effective treatment strategy in patients with both NAFLD and T2D, although further research is required to optimise these interventions and determine their scalability.